EEG signal analysis before and after performing salat on gamma band / Farid Shiman - Farid, Shiman (2012)
Religious meditations and prayers were seen as the conditions necessary for promoting relaxation, healthy living, and acting as alternative medical therapies for balancing human mind and body. In this study, the investigation of all the neuropsychophysiological effects of pre- and post-baseline of an Islamic prayer (Salat) on the electroencephalogram (EEG) was carried out. The EEG data in this study were recorded for ten healthy males for pre- and post-baseline in the performance of the Salat. In order to analyze the data from the EEG signals of this study, AcqKnowledge 4.0 software (BIOPAC Systems Inc, Goleta, CA) and Matlab were used to compute and analyze the power spectral density (PSD) data (in µv²) for the Gamma (30-60 Hz) band. The results show that the gamma EEG power has significant increase in post-baseline compared to the pre-baseline. The statistical analysis (paired t-test) indicated that there was significant increase of gamma power in the frontal and occipital channels.Additionally, meditation in Salat in the forms of Focus Attention (FA) and Transcendetional Meditation(TM) were introduced for the first time as cognitive processes and EEG pattern in this study. This study further revealed that there are physiological changes during meditation which in turn suggested that there is wakeful hypometabolic state which has the qualities of decreasing the sympathetic nervous activity but increasing parasympathetic activity.